Natural history of the rare and endangered snake Atractus ronnie (Serpentes: Colubridae) in northeastern Brazil - Ferreira-Silva, Cristiana [UNESP]; Ribeiro, Samuel Cardozo; Alcantara, Edna Paulino de [UNESP]; Avila, Robson Waldemar (Univ Sao Paulo, Esalq, 2019)
The habitat use, activity period, sexual dimorphism, morphological variation, reproduction and diet composition of this fossorial and nocturnal snake are reported. The snakes were captured between 2008-2014 in the Chapada do Araripe in northeastern Brazil, and were collected by active visual searches, as well as in pitfall traps with drift fences. Although females are larger than males, the males have longer tails, and scale counts differ between the sexes. Reproduction is seasonal, occurring during the rainy season. Brood sizes rang from one to four eggs. Atractus ronnie preys on earthworms, in addition to ants (Crematogaster sp.) and insect larvae.
Keywords: Cerrado; diet; sexual dimorphism; habits; reproduction